Occurrence and bioaccumulation of organophosphate flame retardants in high-altitude regions: A comprehensive field survey in Qinghai Province, China - Haibao Zhu; Jinlin Hu; Zheng Ruan; Danhua Liu; Meirong Zhao (Ecotoxicology and Environmental Safety)
Organophosphate flame retardants (OPFRs) are a class of substances that pose potential risks to human health and ecosystems due to their large-scale production, wide range of applications, and ubiquitous presence in the environment. With their potential for long-range atmospheric transport (LRAT), OPFR pollution in high-altitude areas has become an increasing concern. Herein, a general pretreatment method for OPFRs across various sample matrices was established and combined with gas chromatography-mass spectrometry (GC-MS), utilizing a programmed temperature ramp in the vaporization chamber to enable high-throughput detection of OPFRs in various environmental matrices. OPFRs were quantified in soil, grass, tree bark, and wild rat liver samples collected from Qinghai, China (elevation: 2657–4635 m), and their occurrence and bioaccumulation behaviors were systematically investigated. All samples were contaminated with OPFRs, with ∑OPFR concentrations showing the trend of rat liver (mean: 439 ng/g, median: 420 ng/g) > grass (mean: 338 ng/g, median: 273 ng/g) > soil (mean: 190 ng/g, median: 162 ng/g) > tree bark (mean: 125 ng/g, median: 116 ng/g). Paired sample Spearman correlation analysis showed that soil ∑OPFRs were significantly positively correlated with grass ∑OPFRs (P = 0.0023), indicating that soil is the main source of OPFRs in grass. Among soil, grass, tree bark, and rat liver samples, tris(2-chloroisopropyl) phosphate (TCIPP) and tris(2-chloroethyl) phosphate (TCEP) had the highest contribution rates to ∑OPFRs, with cumulative contributions of 60.9 %, 48.6 %, 76.5 %, and 71.1 %, respectively, indicating that the proportion of industrial sources of OPFRs reaching this area through LRAT is relatively high. Biomagnification factor (BMF) analysis revealed that ∑OPFRs exhibited significant bioaccumulation and biomagnification effects within the soil-grass-rat terrestrial food chain. The ecological risk assessment results indicated that ∑OPFRs in the soil of the study area pose a high ecological risk, with aryl-OPFRs posing the greatest risk. Our findings provide a crucial foundation for further investigation into the contamination and bioaccumulation characteristics of OPFRs in high-altitude regions.